Wajh al-Munāsabāt fī Sūrah al-Fātiḥah ‘inda Muḥammad al-Ṭāhir bin ‘Āsyūr - Sujiat Zubaidi Saleh; Ummu Salamah (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2017)
This paper will research the content of al-Qur'an by finding some correlations between the arrangement of words, sentences and verses with 'ilm al-muna>sabah, so it will clarify the meaning contained therein. 'Ilm al-muna>sabah has an important role in studying interpretation of al-Qur'an. Over time, most of the orientalists and Muslim liberals want to deconstruct the content of al-Qur'an. They spread negative assumptions, that the verses of al-Qur’an and its chapters are not systematic. According to them, it is because the verses of al-Qur’an and its chapters are incompatible with systematic scientific writing, and the displacement of a group of verses to another group has not been synchron. Based on this reason, Ibnu Asyur tries to apply 'ilm al-muna>sabah to interpret al-Qur'an to show maqa>s}id al-Qur’a>n. Then he also proved that the non-systematic al-Qur'an had become one of i'jaz al-Qur'a>n. If the way how Ibnu Asyur analyzed 'ilm al-muna>sabah is observed deeply, it is known that he used 'ilm al-dala>lah (semantics) as his methodological approach, although it is not mentioned in his methodology of interpretation. In al-Fa>tih}ah, for example, he describes their editorial harmony between one verse to another. Even more, it is found among chapters in al-Qur'an, from the first verse to the last one, in explaining the purification of tawhid, and how it is correlated with